Quality Control in Journalism: The Management of Media Accountability in Newsrooms in Kenya. Issue 3 (1st October 2020) - Obuya, Jared
ABSTRACT: Media organizations are experiencing unprecedented technological, financial, and technological pressures, which have exposed them to severe public scrutiny and put their management practices on the spotlight. In many democratic contexts, media practitioners have responded to these public pressures by instituting a raft of quality control measures aimed at gaining public support and forestalling government interference. This article makes a contribution to these discussions by presenting the results of an investigation of the internally instituted management practices aimed at enhancing media accountability at two newsrooms in Kenya. The study involved semi-structured interviews with purposively selected media managers and journalists and a review of internal documents, which were then analyzed thematically. The results point to weak management systems of the instituted media accountability practices. Consequently, there are perceptions among journalists and media managers that the existing management practices and structures are not sufficient in achieving the level of accountability desirable in a liberal media environment such as Kenya.